Social entrepreneurship education: A combination of knowledge exploitation and exploration processes - Valentina Ndou (Administrative Sciences, 2021)
It is widely accepted that entrepreneurship education has become a key development priority for coping with uncertainty and for addressing various social, economic, and technological concerns related to health, living conditions, education systems, employment, and economic growth. In recent times we have witnessed a proliferation of Entrepreneurship Education (EE) programs and initiatives with the aim to promote the creation of new skills, competencies, and capabilities to deal with a wide range of social issues and for creating new societal. The COVID-19 pandemic situation has introduced radical challenges to the society and has impacted significantly, especially the process of entrepreneurial competencies, skills and attitudes development. This paper aims to provide insights into knowledge mechanisms and learning strategies that have been activated for the effective creation of entrepreneurship competencies. We have based our evaluation on an exploratory analysis of 10 program studies that deliver social entrepreneurship education. The paper presents elements of originality under two perspectives: it proposes a framework with the main patterns characterizing social entrepreneurship education (SEE), and it argues that the creation of an entrepreneurship mindset and competencies is an evolutionary process that combines dynamic knowledge exploitation and exploration mechanisms.
Keywords: 350; case studies; entrepreneurship education; knowledge exploitation; knowledge exploration; social entrepreneurship